Introduction to naval architecture - Tupper, E. C. (Elsevier, 2013)
This book provides a broad appreciation of the science and art of naval architecture, explaining the subject in physical rather than in mathematical terms. While covering basic principles, such as hull geometry, propulsion, and stability, the book also addresses contemporary topics, such as computer-aided design and computer-aided manufacture (CAD/CAM). It reflects the continuing developments in technology, changes in international regulations, and recent research.